The role of general practitioner in the study of adverse drug reactions epidemiology in ambulatory care setting - Turabian, Jose Luis (Archives of Community Medicine and Public Health, 2019)
Adverse drug reactions (ADRs) cause considerable mortality and morbidity. Its importance becomes greater in relation to the current increase in the use of drugs and multimorbidity. Premarketing studies do not allow a complete knowledge of the safety of a medicine. Many ADRs occurring in the outpatient setting, but there is a significant lack of information regarding the epidemiology of ADRs in this level of health care. Thus, guidance on how to direct attention to effective targets for improvement of medication safety in ambulatory care settings is missing. In this scenario, the general practitioner (GP) is in a rare, special position in the health system, which allows him to combine the clinical tasks of diagnosis and treatment on individuals with epidemiological and public health tasks on communities, including a important role in the study of ADRs’s epidemiology. Among the methods aimed at identifying and quantifying the ADRs, in the GP consultation, we have: 1) Data derived from pure clinical observation; 2) Voluntary spontaneous notification systems; 3) Effective local initiatives for improving the collection of reports on ADRs; 4) Careful epidemiological studies, which may include descriptive studies (cross-sectional), retrospective (case-control), prospective (cohort), clinical trials, and single-case studies, seasonal variations, longitudinal studies, etc.; 5) Patient reporting of ADRs; 6) The use of algorithms for the diagnostic of ADRs; 7) Intensive telephone surveillance; 8) Collaborative work with Pharmacists working in the community; 9) From the position of the GP (where the entire medical care process begins and ends) the incidence rate of ADRs caused by hospital prescribed drugs can also be observed and collected from discharge of the hospital admissions; And 10) Genetics and electronic health records can go together to identify heritable traits to predisposition to ADRs. “The scientific purist, who will wait for medical statistics until they are nosologically exact, is no wiser than Horace’s rustic waiting for the river to flow away.” Major Greenwood, 1948.